Behavior assessment based selection method for service oriented applications integrability - Garriga, Martín (2012)
Service-Oriented Computing promotes building applications by consuming reusable services. However, facing the selection of adequate services for a specific application still is a major challenge. Even with a reduced set of candidate services, the assessment effort could be overwhelming. On previous work we have presented an approach to assist developers on the selection of services from a syntactic viewpoint of a matchmaking process for interfaces compatibility. In this paper we extend the approach to assess the behavior of services taking advantage of a black-box testing framework to verify compatibility on the expected execution behavior of a candidate service. This paper analyzes the selection method through a case study, to show its potential on determining the best choice of a service among a set of candidates.